Hattat Bestekârlar - Coşgun, Bilal Enes (My University, 2023)
Yaratıcılık ve hayal gücünün bir ifadesi olarak sanat; her inançta, kültürde ve toplulukta var olmuştur. Onun var olduğu inançlardan biri de İslâm dinidir. İslâm dininin nüzulü ile beraber yaratıcının kulları ile iletişim kurma vasıtası Peygamberine indirdiği Kur’an-ı Kerim ile olmuştur. Okunması ile ibadet edilen bu yüce kelamın varlığı bu dinin inananlarınca gerek sesli gerekse yazılı olarak ifade edilmiştir. Bu ifadelerin daha güzel kılınma gayretinin bir sonucu olarak İslâm’da musıkî ve hat sanatları ortaya çıkmıştır. İslâm ve sonrası dönemlerde musıkî Cahiliye dönemine ve önceki dönemlere nazaran daha dini bir karakter arz etmektedir. İslamiyet öncesi dönemlerde musıkîde def, bendir gibi ritim odaklı sazlı musıkî ön plana çıkarken İslâm sonrası dönemde ritim sazlarının yanında telli ve üflemeli sazların da kullanımıyla beraber daha çok insan sesine dayalı (vokal) ya da sözlü musıkî ön plana çıkmaktadır. Diğer yandan Kur’ân’ın yazılı ifadesine duyulan tazim ve hürmetin sonucunda da Arap yazısını daha güzel ve estetik ifade etme gayreti ile beraber hüsn-i hat sanatı ortaya çıkmıştır. Kökeni Nabatî ve Aramî halklarıyla birlikte Fenike Alfabesinden gelen Arap yazısı İslâmiyet ile beraber kutsal metnin Arap dilinde indirilmesi ile dini bir hüviyet arz etmeye başlamıştır. Bu çalışmada tarihte Türk müziği yapan hattatlardan musıkî sanatında eserler ortaya koymuş olan 49 adet hattat bestekârın isimleri ve biyografileri kronolojik bir sıra gözetilerek verilmiştir. XIII. yy.’da Safiyyüddin el-Urmevi (v.1294) ile ile başlatmış olduğumuz Hattat Bestekârlar XXI. yy.’da yaşayan son hattat bestekâr Erol Dönmez (d.1965) ile nihayete erdirilmiştir. Eserin ekler bölümünde sırasıyla sanatçıların -varsa- fotoğrafına, hat ve beste örneğine yer verilmiştir. Ek-2’de ise sanatçılara ait tüm besteler kaynaklardan taranmış olup 1699 adet eserin listesi “Bestekâr- Güftekâr- Güftenin ilk satırı- Makam- Usul- Form- Referans” sırası gözetilerek tasnif edilmiştir. İlgili çalışmanın Türk Din Musıkîsi alanına katkı sağlayacağı düşünülmektedir.

Art as an expression of creativity and imagination; It has existed in every faith, culture and community. One of the beliefs in which he exists is the religion of Islam. Along with the revelation of the religion of Islam, the creator's means of communicating with his servants was through the Qur'an, which he sent down to his Prophet. The existence of this lofty word, which is worshiped by reading it, has been expressed by the believers of this religion both verbally and in writing. As a result of the effort to make these expressions more beautiful, music and calligraphy emerged in Islam. In the Islamic and post-Islamic periods, music has a more religious character compared to the Ignorance period and previous periods. In pre-Islamic periods, rhythm-oriented musical instruments such as def and bendir came to the fore, while in the post-Islamic period, vocal or verbal music came to the fore with the use of stringed and wind instruments in addition to rhythm instruments. On the other hand, as a result of the veneration and respect for the written expression of the Qur'an, the art of calligraphy emerged with the effort to express the Arabic script more beautifully and aesthetically. The Arabic script, whose origins came from the Phoenician alphabet together with the Nabataean and Aramaic peoples, began to have a religious identity with the downloading of the holy text in the Arabic language together with Islam. In this study, the names and biographies of 49 calligrapher composers who produced works in the art of music, among the calligraphers who made Turkish music in history, are given in a chronological order. XIII. Calligrapher Composers XXI, which we started with Safiyyüddin al-Urmevi (v.1294) in the 19th century. It was finalized with the last calligrapher and composer Erol Dönmez (b.1965) who lived in the 19th century. In the appendix section of the work, photographs of the artists, if any, and examples of calligraphy and composition are given respectively. In Annex-2, all the compositions belonging to the artists were scanned from the sources and the list of 1699 pieces was classified according to the order of Composer- Guftekar- First line of the lyrics- Maqam- Method- Form- Reference. It is thought that the related study will contribute to the field of Turkish Religious Music.
Keywords: Beste; Bestekâr; Calligrapher; Calligraphers; Calligraphy; Composer; Composition; Dini musiki; Hat; Hattat; Hattatlar; Music; Musicians; Musiki; Müzisyenler; Religious music